If that means log 'base 10' then,
log (y) + 2*log (x) = 2
Recall that we can rewrite the number that is multiplied by the the log expression as exponent of the term inside the log. For instance,
a * log (x) = log (x^a)
Thus,
log (y) + log (x^2) = 2
Recall that when log expressions with the same base are added, the terms inside the log can be multiplied and condensing everything to a single log. Thus,
log (y * x^2) = 2
We can raise 10 by both sides:
10^(log (y * x^2)) = 10^2
y * x^2 = 100
y = 100 / x^2
hope this helps~ `u`
Log10y+2log10x=2,express y in terms of x
4 answers
This is a very useful site, thanks for helping!:)
Thanks for helping again! *_*
Loved it!<3
Loved it!<3
If log10y + 3log10x=2 express y in terms of x